Village chickens can strengthen community resilience in the face of insecurity and climate change in Burkina Faso - Dione, Michel M.; Ilboudo, Guy S.; Ouedraogo, Brice; Ima, S.A.; Kagambèga, A.; Ganser, C.; Boz, Z.; Knight-Jones, Theodore J.D.; Alders, R. (World Poultry Science Association, 2025)
In countries like Burkina Faso where climate change and political insecurity are causing displacement of communities to safer areas, village chickens are commonly raised by rural households. Indigenous chickens are well-adapted to local conditions due to their heat tolerance, ability to scavenge when access to feed is limited, and the relative ease of transport to market or to relocate during instability. Chicken production is a potential avenue to strengthen community resilience. To assess the roles and production practices for chickens in the communities, we carried out focus group discussions with 98 men and 99 females in 10 villages and a household survey in 483 chicken keeping households across 23 villages in Boussouma commune, a typical rural setting in Burkina Faso. Results show that the chicken production system is mainly extensive scavenging. The mean size of flocks was 42 birds (min= 1 bird, max=155 birds). However, most farmers (81%) keep 5 to 50 birds with little or no supplementary feeding and rudimentary housing. Seventy-six percent of farmers said that the main reason for keeping chicken is for sale to generate household income; a few indicated they kept chicken for household consumption (9%), and even fewer for egg consumption (2%). There is a significant association between the purpose of chicken keeping and the farmer’s main income generating activity. Most revenue from chicken sales is spent on household health (29%), food (21%) and education (20%). While men spent more revenue from chicken production on agriculture and household equipment, women spent more on food for the household, education and medical expenses. Chicken ownership is not restricted by gender and sex; however, women are more involved in the day-to-day flock husbandry with limited decision-making on chicken sales. Most producers indicated that Newcastle disease (ND) is the main cause of chicken mortality, with 59% of farmers saying their birds had been affected by disease compatible with ND in the three months prior to the survey. Poor or absence of adequate chicken housing, poor feeding and limited access to veterinary services were cited as key challenges. Village chicken plays a major role in strengthening resilience for communities that face high poverty with fragile production systems due to recurrent drought, heat stress and insecurity. This is largely through low-input, flexible means of household income generation, yet this could be greatly enhanced. With locally adapted interventions that employ a One Health approach, production of village chicken has the potential to secure and greatly improve smallholder livelihoods and household food security, while preserving public health in Burkina Faso.